2012
DOI: 10.1371/journal.pone.0048478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Immunosuppressive Treatment in the GRMD Dog Model of Duchenne Muscular Dystrophy

Abstract: The GRMD (Golden retriever muscular dystrophy) dog has been widely used in pre-clinical trials targeting DMD (Duchenne muscular dystrophy), using in many cases a concurrent immune-suppressive treatment. The aim of this study is to assess if such a treatment could have an effect on the disease course of these animals. Seven GRMD dogs were treated with an association of cyclosporine A (immunosuppressive dosage) and prednisolone (2 mg/kg/d) during 7 months, from 2 to 9 months of age. A multi-parametric evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 43 publications
3
45
0
Order By: Relevance
“…Indeed, gait speed is widely used as an outcome measure in clinical trials for muscular dystrophy [2635]. Gait abnormalities have also been reported in canines with Duchenne muscular dystrophy and other myopathies [19, 27, 3640]. Some measures of muscle strength and respiratory function have already been reported in the XLMTM dog [13, 41], but this is the first study of gait assessment in this large animal model and the first assessment of awake animals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gait speed is widely used as an outcome measure in clinical trials for muscular dystrophy [2635]. Gait abnormalities have also been reported in canines with Duchenne muscular dystrophy and other myopathies [19, 27, 3640]. Some measures of muscle strength and respiratory function have already been reported in the XLMTM dog [13, 41], but this is the first study of gait assessment in this large animal model and the first assessment of awake animals.…”
Section: Discussionmentioning
confidence: 99%
“…In canine DMD, treatment with CysA and prednisone demonstrated a mixed outcome with improvement in some muscle characteristics but worsening of others. Improvements were observed in motor scores, gait analysis, and possibly contracture relief, but these were offset by the worsening of force measurements (although this may be due to possible measurement artifact) and worsening of histopathology (with an increase in calcified myofibers) (82). …”
Section: Therapeutic Opportunities In Dmdmentioning
confidence: 99%
“…Glucocorticoids are the most commonly used drug in DMD patients. Several groups have tested prednisone in affected dogs (167)(168)(169). These studies revealed some beneficial effects, such as improvement in gait, increase of the extensor muscle force, and elevation of the integrin level.…”
Section: Therapeutic Testing In the Canine Model And Impact On Patienmentioning
confidence: 99%